Diversity of Soybean (Glycine max [L.] Merr.) in Java based on Planting Sites - SRI ROSSATI SETYA WIRAWAN (Biodiversitas Journal of Biological Diversity, 2000)
The research was to find out similarity among soybean (Glycine max [L.] Merr.) cultivars in Java based on site planting by morphological taxonomy evidences. Fresh samples of soybean were collected from 20 sites in Java and 20 samples were collected in every site. Soybean was observed at flowering and seed maturing time. The similarity wasdetermined by Euclidean distance and clustered by average linkage. The result showed that soybean from Bantul wassplit by another 19 cultivars. The remaining cultivars were split into two groups. The first, i.e.: Tangerang, Garut, Wonogiri, Klaten, and Sukoharjo, and the second, i.e. Tuban, Wonosari, Pasuruan, Pati, Karawang, Yogyakarta, Sumedang, Purwokerto, Wates, Bojonegoro, Lumajang, Ngawi, Sleman, and Sukabumi. They were split into several little groups. The cultivars between Tuban and Wonosari, Ngawi and Sleman, also Tangerang and Garut had closed relationships. Keywords: soybean, planting site, relationship.